2005
DOI: 10.1007/s00213-005-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of ecstasy/polydrug use on executive components: shifting, inhibition, updating and access to semantic memory

Abstract: Rationale/Objectives: Recent theoretical models suggest that the central executive may not be a unified structure. The present study explored the nature of central executive deficits in ecstasy users. Methods: In Study One, 27 ecstasy users and 34 nonusers were assessed using tasks to tap memory updating (computation span; letter updating) and access to long-term memory (a semantic fluency test and the Chicago word fluency test). In Study Two, 51 ecstasy users and 42 nonusers completed tasks that assess mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 66 publications
4
91
1
2
Order By: Relevance
“…Research from our laboratory has previously demonstrated that ecstasy users are impaired on executive function (spatial working memory- Wareing et al 2004, memory updating-Montgomery et al 2005a, access to semantic memory- Montgomery et al 2005a) and other working memory/executive based tasks (associative learning- Montgomery et al 2005b, syllogistic reasoning-Fisk et al 2005Montgomery et al 2005c). Similar findings have been observed by other authors (see Morgan, 2000, for a review of the literature).…”
Section: Introductionmentioning
confidence: 99%
“…Research from our laboratory has previously demonstrated that ecstasy users are impaired on executive function (spatial working memory- Wareing et al 2004, memory updating-Montgomery et al 2005a, access to semantic memory- Montgomery et al 2005a) and other working memory/executive based tasks (associative learning- Montgomery et al 2005b, syllogistic reasoning-Fisk et al 2005Montgomery et al 2005c). Similar findings have been observed by other authors (see Morgan, 2000, for a review of the literature).…”
Section: Introductionmentioning
confidence: 99%
“…not being entirely accurate, not least given the implications for memory deficits with drug use. However due to the legal status of the drug being investigated, this is the most appropriate method for attaining an estimate of lifetime drug use and is the most commonly used method in the literature investigating drug use and cognition (Fox et al, 2001;Montgomery et al, 2005;Montgomery et al, 2010). Additional uncertainty about purity of ecstasy tablets consumed, as well as cocaine purity and cannabis strength cannot be assured.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of total lifetime drug use of each drug were calculated (as per Montgomery et al, 2005) as well as totals for last 30 days drug use and weekly drug use estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Drug and alcohol use was assessed via a self-report questionnaire (Montgomery et al, 2005). Participants are asked about the frequency and intensity of ecstasy, cannabis, alcohol, cocaine, amphetamine and other drug use, and their responses are used to calculate scores for frequency of use, total lifetime amount used, average weekly amount used, abstinence, length of use and recent use.…”
Section: Methodsmentioning
confidence: 99%
“…This is not unusual in studies of this type and many published ecstasy use studies rely on self-report and do not use objective measures (e.g. Fox et al, 2002;Montgomery et al 2005;Rodgers, 2000). In support, a recent study has demonstrated that self-reported use of ecstasy is consistent with the levels of MDMA obtained from hair samples (Scholey et al, 2011).…”
Section: Diurnal Cortisolmentioning
confidence: 99%